Basic Badminton Techniques in Physical Education: A Literature Review - Ishak, Muhammad (Journal of Sport Education, Coaching, and Health (JOCCA), 2025)
Learning badminton as part of the physical education curriculum has great potential to develop students' motor skills, coordination, and sportsmanship. However, the effectiveness of learning basic techniques—such as serving, footwork, smashing, lobbing, and netting—is highly dependent on the learning model and media used. This systematic literature review analyzed 25 studies from 2014–2024 that evaluated various badminton learning models at the school level (elementary, middle, and high school), including traditional methods (drill, demonstration), modern methods (TGFU, game-based learning, hybrid), and the use of video/multimedia media. The analysis showed that TGFU and game-based learning models most consistently produced significant improvements in basic technique mastery and tactical understanding. Serving and footwork techniques showed the highest improvements, with training effectiveness and effect sizes in the medium to large categories. Multimedia-based learning has also been shown to accelerate movement comprehension and increase student motivation. However, learning success is often limited by the condition of facilities/infrastructure, large student numbers, and teacher capacity to implement new models. Based on these findings, a blended pedagogy strategy is recommended for physical education teachers, encompassing a combination of drills, game-based learning, and visual media—supported by a performance assessment rubric and small group work—to optimally master basic badminton techniques within the context of school education. This study provides a theoretical and practical basis for developing adaptive, effective, and relevant badminton instruction that addresses student characteristics and the demands of a modern curriculum.